Next‐generation sequencing for BCR‐ABL1 kinase domain mutations in adult patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia: A position paper - Simona Soverini; Francesco Albano; Renato Bassan; Francesco Fabbiano; Felicetto Ferrara; Robin Foà; Attilio Olivieri; Alessandro Rambaldi; Giuseppe Rossi; Simona Sica; Giorgina Specchia; Adriano Venditti; et al. (Cancer Medicine, 2020)
Abstract Emergence of clones carrying point mutations in the BCR‐ABL1 kinase domain (KD) is a common mechanism of resistance to tyrosine kinase inhibitor (TKI)‐based therapies in Philadelphia chromosome‐positive (Ph+) acute lymphoblastic leukemia (ALL). Sanger sequencing (SS) is the most frequently used method for diagnostic BCR‐ABL1 KD mutation screening, but it has some limitations—it is poorly sensitive and cannot robustly identify compound mutations. Next‐generation sequencing (NGS) may overcome these problems. NSG is increasingly available and has the potential to become the method of choice for diagnostic BCR‐ABL1 KD mutation screening. A group discussion within an ad hoc constituted Panel of Experts has produced a series of consensus‐based statements on the potential value of NGS testing before and during first‐line TKI‐based treatment, in relapsed/refractory cases, before and after allo‐stem cell transplantation, and on how NGS results may impact on therapeutic decisions. A set of minimal technical and methodological requirements for the analysis and the reporting of results has also been defined. The proposals herein reported may be used to guide the practical use of NGS for BCR‐ABL1 KD mutation testing in Ph+ ALL.